The Effect of Backpack Weight on Cardiovascular and Respiratory Changes in Adolescent Students - hossein hosseini; hasan daneshmandi; farhad rahmani nia (Sport Sciences and Health Research)
The purpose of this study was to examine cardiovascular and respiratory changes in students carrying backpacks. 15 male students (age: 12.5±0.5 years old; height: 164.7±1.8 cm; and weight: 55±1.6 kg) volunteered to participate in this study. All subjects randomly carried backpacks of 0%, 8%, 10.5% and 13% of their own body weight in different days on treadmill at 3.9 km/h for 15 minutes. Heart rate (HR), pulmonary ventilation (VE) and frequency respiration (FR) of the subjects were measured by Gas Analyzer System and SBP and DBP were measured by a digital blood pressure meter in 3 positions: test, exercise (15th minute) and recovery (3 minutes after walking). The statistical analysis of data indicated that SBP, DBP and VE in 10.5% and 13% load conditions were significantly higher than in 0% and 8% load conditions (P=0.000). Also, 10.5% and 13% load conditions were significantly higher 3 minutes after walking when compared to the rest level (P=0.000). There were no significant differences between 0% and 8% load conditions in both during and 3 minutes after walking conditions. HR and FR of subjects showed no significant difference during and after carrying different loads. According to the results of the present study, carrying backpacks equal to 8% of body weight does not create any significant changes in cardio-respiratory parameters of students, thus it can be recommended as an optimal weight of backpack for students.